Nurses' performance in natural disasters situations: an integrative review (Research, Society and Development, 2022)
Disasters can happen due to several natural phenomena, sometimes by the joining of two or more, being classified as technological or natural. These adverse events usually affect people who are already in a vulnerable situation, and may be directly related to psychological disorders, and may also affect professionals. The work aimed to analyze, based on the scientific literature, the role of nurses in situations of natural disasters. This is an Integrative Review (IR) literature search of the literature, which used the Descriptors in Health Sciences (DeCS) and the titles of the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Mesh terms. In all, eleven studies were selected, most of which presented a qualitative approach to data, corresponding to seven (63.3%) works, in which the National Library of Medicine database had the largest number of studies (45.4%). Most publications focused on the year 2019 (36.3%) and 2020 (27.2%). As for the language, ten (90%) of the publications were in English; where Brazil was the country with the highest number of publications (27.2%). The assistance provided to patients victims of natural disasters should be focused on physical and psychological aspects. In this case, nursing must take action by dealing directly with the subject and providing clarifications about the procedure performed by him, in addition to performing active listening, when the patient is able and willing to verbalize, offer comfort and use touch as a source of security for customers.